Denosumab prevents acetabular bone loss around an uncemented cup: analysis of secondary outcomes in a randomized controlled trial. - KIRITOPOULOS, Demostenis; NYSTRÖM, Andreas; ULLMARK, Gösta; SÖRENSEN, Jens; PETRÉN-MALLMIN, Marianne; MILBRINK, Jan; HAILER, Nils P.; MALLMIN, Hans (Acta Orthopaedica, 2022)
Background and purpose -- Uncemented total hip arthroplasty (THA) is associated with periprosthetic bone loss. In a secondary outcome analysis from a randomized controlled trial, we studied whether denosumab can prevent loss of acetabular periprosthetic bone mineral density (pBMD) in patients who received a trabecular metal cup during uncemented THA. Patients and methods -- 64 patients (aged 35--65 years) with unilateral osteoarthritis of the hip were randomized to 2 subcutaneous injections with denosumab or placebo, given 1--3 days post-surgery and 6 months post-surgery. Acetabular pBMD was measured in 5 regions of interest (ROIs) by dual-energy X-ray absorptiometry. Serum markers for bone metabolism were analyzed. Periprosthetic osteoblastic activity, measured as standardized uptake values (SUVs) by [18F] positron emission tomography/computed tomography, was evaluated in 32 of the 64 study patients. Results -- After 12 months, patients treated with denosumab had higher pBMD compared with the placebo-treated patients in 4 of 5 ROIs and in sum of ROIs 1--5. After 24 months, the effect on pBMD for patients treated with denosumab declined. Serum markers declined pronouncedly up to 12 months in patients treated with denosumab, but rebounded above baseline levels after 24 months. Patients treated with denosumab had statistically significantly lower SUVs in all ROIs, except ROI 5, after 6 months. Interpretation -- Based on this exploratory analysis of secondary endpoints the application of denosumab seems associated with preserved acetabular pBMD, reduced bone metabolism and attenuated periprosthetic osteoblastic activity. However, given the known rebound affects after discontinuation of denosumab treatment, these effects cannot be expected to persist. If prolonged treatment or shift to other regimes would be beneficial to reduce the risk of cup loosening is yet to be investigated.